Antagonistic Drug-herb Interactions between Clinacanthus nutans and Cyclophosphamide on WRL 68 Cell Line - Abd Mutalib, Nurliana; Abd Latip, Normala (Pharmaceutical Sciences and Research, 2020)
Clinacanthus nutans (Acanthaceae), locally known as Sabah snake grass, is popularly taken as prevention as well as treatment for cancer in Malaysia, despite lack of concrete clinical evidence. However, it is crucial to evaluate potential antagonistic, additive, or synergistic interactions that may result from the co-treatment of this plant in chemotherapy. In this study, we demonstrate the drug-herb interaction using combination treatment of C. nutans extracts and cyclophosphamide on the WRL 68 cell line. Materials and Methods: Aqueous and 70% ethanol extract of C. nutans leaves were prepared using decoction and maceration methods. MTT assay was used to test single treatment as well as the combination of C. nutans extract and cyclophosphamide. Phytochemical profiling and flavonoid were identified using HPLC. Results: C. nutans ethanolic extract exhibits low antiproliferative activity. A combination of ethanolic extract of C. nutans and cyclophosphamide at various concentrations resulted in antagonism with combination index values of 1.413, 1.482, and 1.525. Flavonoids identified in the phytochemical profile of both extracts were schaftoside, isoorientin, orientin, and vitexin. High flavonoids level in C. nutans ethanolic extract could potentially interact with metabolic enzymes of the cell line, which might have affected metabolism and activated the cyclophosphamide. The in vitro data suggested that there was a potential for drug-herb interactions, which could negatively affect the chemotherapeutic outcomes. Further investigation should be done in vivo and clinical research model.